GENETIC CARACTERISTICS OF ROTAVIRUSES GROUP A CIRCULATING IN THE ОRENBURG REGION IN SEASON 2016—2017 - N. B. Denisyuk (Детские инфекции (Москва))
The results of genotyping of feces from 53 childrens with rotavirus infection are presents. The techniques of enzyme-linked immunosorbent assay and polymerase chain reaction were applied. In the Orenburg region, during epidemic seasons (2016—2017) 6 genotypes of rotaviruses group A were circulating. The frequency of detection of genotypes [P]G of rotaviruses group A was as follows: G9[P]8 — 54.7%; G4[P]8 — 26.4%; G2[P]4 — 9.5%; G1[P]8 — 5.6%; G3[P]8 — 1.9%, GХ[P]8 — 1.9%. The dominant genotype alternatives of rotaviruses are detected and their regional diversity of combinations. The genotypes G9[P]8 and G4[P]8 were presented as the most frequently occurring in this period. The clinical characteristics of rotavirus infection in children depending on genotype in different age groups is established.